Implementation Method of GEO and LEO Satellite Tracking Compatible Flat-Plate Antenna - Jian CHEN; Zhengqian ZHANG; Xinsheng MA; Ting CHAO; Gangtao GUO (天地一体化信息网络)
In order to improve the portability, disassembly and usability of the satellite communication antenna products in the fi eld, a GEO and LEO satellite tracking compatible fl at-plate antenna implementation method was proposed, the micro strip array antenna was integrated with the radio frequency channel, and the radio frequency of the antenna was fl at and integrated, combined with the high density multi-layer vertical interconnection technology, the whole machine was small in size, light in weight and low in power consumption, and the tracking control unit could satisfi ed the requirements of GEO Beacon and carrier tracking, also could satisfi ed the LEO analysis and the program guidance tracking.The antenna did not need manual assembly and disassembly, and could be used for satellite communication with onebutton deployment.high-precision tracking and stable communication could be achieved for GEO, MEO and LEO satellite.